The Role of Shidiq Values in Islamic Leadership on The Performance And Sustainability of MSMEs: A Literature Study - Ari Prasetyo (Universitas Islam Darul 'ulum Lamongan, 2026)
Leadership in Micro, Small, and Medium Enterprises (MSMEs) is not only determined by technical capabilities, but also by ethical values and integrity, where one of the main principles in Islamic leadership is shidiq (honesty) as a foundation in building trust, maintaining business relationships, and ensuring business sustainability; however, studies that specifically place shidiq as a key element of leadership in MSMEs are still limited. This study aims to analyze the role of shidiq in Islamic leadership and examine its impact on the performance and sustainability of MSMEs. This study uses a qualitative descriptive approach with a literature study method, with data obtained from various relevant scientific sources in the last ten years and analyzed using a thematic analysis approach. The results show that shidiq has an important role in shaping leadership with integrity, transparency, and accountability, which is able to increase customer trust, strengthen employee loyalty, build an ethical organizational culture, and contribute to improving the performance and sustainability of MSMEs through improving business reputation and organizational stability.